2021
DOI: 10.1007/s00120-021-01479-8
|View full text |Cite|
|
Sign up to set email alerts
|

Selbstuntersuchung von Hoden und Brust – eine retrospektive Kohortenstudie an Medizinstudierenden

Abstract: Zusammenfassung Hintergrund Durch eine regelmäßige Selbstuntersuchung kann ein Malignom der Hoden oder Brust gegebenenfalls frühzeitig erkannt und kurativ behandelt werden. Ziel dieser Arbeit war es, das Selbstuntersuchungsverhalten von Medizinstudierenden zu untersuchen und Faktoren, die eine regelmäßige Selbstuntersuchung beeinflussen, zu identifizieren. Methodik Medizinstudierende wurden mittels Fragebogen bezüglich ihres Gesundheits- und … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This attitude toward a healthy preventive self-awareness is a problem which is independent of age but based on gender difference. A study among medical students from Munich showed that comparing breast cancer and TC women performed self-examinations of their breasts more frequently (72%) than men performed TSE (64%) [23].…”
Section: Discussionmentioning
confidence: 99%
“…This attitude toward a healthy preventive self-awareness is a problem which is independent of age but based on gender difference. A study among medical students from Munich showed that comparing breast cancer and TC women performed self-examinations of their breasts more frequently (72%) than men performed TSE (64%) [23].…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, the knowledge of young people about testicular tumors and testicular self-examination has been demonstrated to be very low [ 8 ]. A comparison of testicular and breast self-examination showed that girls examined their breasts more often than boys examined their testicles [ 9 ].…”
Section: Introductionmentioning
confidence: 99%